Corporate governance disclosure and earnings quality: study on companies listed on the ASEAN star financial times stock exchange (FTSE) / Robick Faliana and Wiwik Utami - Faliana, Robick; Utami, Wiwik (Universiti Teknologi MARA, 2021)
The governance mechanism is different for each company. Therefore, companies need an indicator to measure the quality of governance and one of them is the ASEAN Scorecard. This indicator is used as a standard for measuring the quality of corporate governance in the ASEAN region. The corporate governance mechanism can be a factor in price changes in the stock market. Investors will react to any issues related to it. Price changes that occur on the stock market are a measure of the size of investors in investing because they can affect expected earnings. Although there is quite a lot of research related to it, research on earnings quality that discusses market response to price changes that occur due to the influence of governance mechanisms is limited. This study aimed to examine the effect of corporate governance on earnings quality using companies listed on the Financial Time Stock Exchange ASEAN Star (FTSE ASEAN Star). The study was conducted by examining financial ratios of companies using a cross-sectional data regression model with the Earnings Response Coefficient (ERC) as a proxy. The results showed that corporate governance affected ERC, especially on the disclosure of corporate governance and shareholder rights.